Impact Of Brand Image, Social Media Marketing, And Service Quality Toward Purchase Decision (Study on Coffeehouse Company: Starbucks) - Wiranoto, Muhammad Bayu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2021)
This research aimed to determine the impact of the Brand Image, Social Media Marketing, and Service Quality toward Purchase Decisions on Starbucks Coffeehouse Company research at Duta Mall Banjarmasin. This research used a sample of 100 respondents in which the survey was conducted through an online and paper questionnaire. The sample of this research consisted of respondents at least 17 years old and the respondents have been Starbucks consumers at Duta Mall Banjarmasin in the last one year period. Multiple Linear Regression and hypothesis testing using t-test and f-test were employed to analyze the data, which was then processed through SPSS software. From the results of testing three hypotheses, it can be concluded that the Brand Image, Social Media Marketing, and Service Marketing have positive and significant influence on Purchase Decision on Starbucks Coffeehouse Company at Duta Mall Banjarmasin. Keywords: Brand Image, Social Media Marketing, Service Quality, Purchase Quality.